Relative stroke length measurement in the tethered swimming test - Reis, G.; Porto, D.; Peres, M.; Nogueira, F. C. A.; Tucher, G. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION The sports training process for water polo and for swimming aims to promote the accumulation of training loads to improve the athlete's performance. Movement can be assessed in different ways, although there are different ways of positioning in the water. Nevertheless, displacement capacity is an indicator of athletes' movement efficiency (Tucher et al., 2016). In this sense, protocols for assessing propulsive force, stroke rate (SR), and stroke length (SL) are important for monitoring and training athletes (Morais et al., 2013). [...]